Answer:
x = (y - b)/m
Step-by-step explanation:
Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.
First subtract b from both sides:
y = mx + b
y (-b) = mx + b (-b)
y - b = mx
Next, divide m from both sides:
(y - b)/m = (mx)/m
x = (y - b)/m
x = (y - b)/m is your answer.
~
Answer:
there is no ecuashon
Step-by-step explanation:
h0cududfiififuduc
Answer:
1. 30/14
2. -26.775
3. 0.1668
4. -44/7 which can be simplified into -6 and -2/7
5. $10.96
Answer:
u divide the area by 3.14
Step-by-step explanation:
it reverses the area